Serology of Toxoplasma gondii in academics of the 2nd year of medicine and its prevalence depending on eating habits - Binder, Ana Lucia; Sá, Kim Fonseca Gomes de; Marques, João Rodrigues Cordeiro; Spanhol, Betania Luz; Paula, Jessica Caroline de; Rebelatto, Amanda Cole; Evers, Sandy; Campos, Beatriz Dias; Sosa, Fatima Marilin Valdez; Bichofe, Anderson Remes (Seven Editora, 2024)
Toxoplasma gondii, the etiological agent of toxoplasmosis, is an obligate intracellular parasite, opportunistic, with worldwide distribution, with the cat as the definitive host and the main responsible for transmitting the parasite through feces. The aim of this research is to find out through the data what are the possible means of contamination and how we can prevent these forms of transmission. This research was conducted at the Universidad Central del Paraguay - Ciudad del Este, Paraguay, during the period of 2021. A total of 114 students from the 2nd year of the medical career were evaluated, evaluated by the Microbiology Chair. The Rapid Test was carried out for the detection  of anti-Toxoplasma Gondii antibodies, in addition to presenting a questionnaire to the students to assess their knowledge about the disease and foster research, the questionnaire covers questions to assist in the exploration of the subject were they about, the foods consumed, sausage or raw, drinking water intake, if there are cats near your home,  if you sleep with pets, knowledge about the disease, family history of toxoplasmosis, form of transmission, clinical manifestations, among others. The serum prevalence found in this research was low, but it was noted that most of the students investigated have bad eating habits such as the consumption of vegetables and foods with poor hygiene, which may be associated with seropositivity for toxoplasma infection, thus encouraging methods for the prevention of the disease is extremely important since it allows us to understand the associated risk factors and develop strategies for the awareness of the general population. DOI:https://doi.org/10.56238/sevened2023.007-009